1978
DOI: 10.1007/bf01870329
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside transport in mammalian cell membranes

Abstract: Transport of the nucleoside analog cytosine-arabinoside (CAR) in transformed hamster cells in culture has been studied in conditions of minimal metabolic conversion. Uptake (zero-trans in) properties at 20 degrees C over a limited range of CAR concentrations were characterized by a Km of 350 micrometer and a maximal velocity (V) of 780 micrometer.min-1 (V/Km = 2.28 min-1). Equilibrium exhcange at 20 degrees C over a wider range of concentrations was best described by a saturable component with a Km of 500 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The growth fraction of leukemic cells is generally considered <1.0 and recent estimates based on nuclear DNA-polymerase activity suggest that less than half the leukemic blasts of marrow are in active proliferation (35,36). Moreover the growth fraction of blasts from peripheral blood may be still lower, since tritiated thymidine labeling indices are considerably less for circulating than for intramedullary blasts (37,38 It is established that araC is a substrate for the nucleoside-specific transport mechanism in the cell membrane (12)(13)(14)39) so that transport rate of araC should relate to the density of transport elements in the cell membrane. The validity of this concept is apparent in the correlation of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth fraction of leukemic cells is generally considered <1.0 and recent estimates based on nuclear DNA-polymerase activity suggest that less than half the leukemic blasts of marrow are in active proliferation (35,36). Moreover the growth fraction of blasts from peripheral blood may be still lower, since tritiated thymidine labeling indices are considerably less for circulating than for intramedullary blasts (37,38 It is established that araC is a substrate for the nucleoside-specific transport mechanism in the cell membrane (12)(13)(14)39) so that transport rate of araC should relate to the density of transport elements in the cell membrane. The validity of this concept is apparent in the correlation of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Movement of nu-cleoside and many of their analogs across the plasma membrane in many cell types is mediated by a nucleoside specific transport mechanism. Cytosine arabinoside is a substrate for this carrier system (11)(12)(13)(14)(15) that is reversible, nonconcentrative, and has a broad specificity for pyrimidine and purine nucleosides. However, the affinity of the nucleoside carrier in leukemic cells is less for araC than for its naturally occurring pyrimidine analog, deoxycytidine.…”
mentioning
confidence: 99%
“…Concentration-effect curves for inhibition of uridine and adenosine transport are biphasic, raising the possibility of interaction of NBMPR with two or more classes of transport-inhibitory sites (Paterson, 1979;Paterson et al, 1980). Kinetic studies of NBMPR inhibition of uridine transport in hamster fibroblasts have indicated that interactions between NBMPR and nucleoside-transport mechanisms are also complex in this cell type (Eilam & Bibi, 1977;Eilam & Cabantchik, 1977;Heichal et al, 1978). Inhibition was partially competitive (K, = 3.7 nM), and a substantial fraction of transport activity (20-30%) was insensitive to increasing concentrations of inhibitor.…”
mentioning
confidence: 99%
“…These data, together with results from studies of the effects of organomercurials on NBMPR inhibition of uridine transport, led Eilam & Cabantchik (1977) to propose that binding of NBMPR occurs at transporter sites different from substrate-binding sites. In a subsequent study (Heichal et al, 1978), four distinct classes of sites on the uridine carrier of hamster cells were postulated: a substrate-binding site, an NBMPR-binding site and two types of thiol-containing modifier sites (one stimulatory, the other inhibitory, after binding of organomercurials).…”
mentioning
confidence: 99%
See 1 more Smart Citation